Strategi Mempopulerkan Makanan Tradisional melalui Proyek Penguatan Profil Pelajar Pancasila (P5) - S. Aniq Qomar; Ghofur Retno Wardani; Lailatul Istikomah; Muhammad Nofan Zulfahmi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze strategies for popularizing traditional food through the Strengthening the Profile of Pancasila Students Project (P5). Traditional food, as part of cultural heritage, is increasingly marginalized by the popularity of modern food among the younger generation. This research employs a library research method by reviewing relevant literature on P5 and the preservation of traditional food. The findings show that implementing P5 with an entrepreneurship theme in elementary schools can enhance students' awareness of traditional food while fostering entrepreneurial values. Activities such as school bazaars and cooking practices contribute to introducing traditional food to students, engaging them in experiential learning, and instilling values of collaboration and creativity. In conclusion, the strategy of popularizing traditional food through P5 is an effective step to preserve cultural heritage while fostering students' character in line with the Pancasila Student Profile.